Methods for Determination of Reactive Metabolites of Thiopurines - Dardan Dreshaj1 , Flaka Pasha2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: This Review Represents A Critical And Constructive Analysis Of Literature In The ContentOf Methods For Determination Of Reactive Metabolites Of Thiopurines. The Review Is Generated ThroughSummary, Classification, Analysis And Comparison Of Already Existing Material And Researches On Field.Methods: Databases As Scopus, Pubmed, Medline And Web Of Science Were Used To Extract Data For TheReview. Search Terms Like “Methods For Determination Of Metabolites”, “Thiopurines” And “ReactiveMetabolites” Were Used. Out Of 160 Research Articles Screened, 20 Most Relevant Studies Are IncludedIn This Review.Conclusion: Determining Thiopurine Metabolites Level Is Crucial On Improving Patients’ Safety, QualityAnd Efficacy Of Treatment, Measure Patients’ Adherence To Therapy, Optimize Thiopurine Dosage ByEither Finding Safer/Higher Doses If Remission Is Not Achieved, Or By Determining Dose ReductionsWhen Adverse Treatment Outcomes Occur.Thiopurine Metabolites Are Measured By High-Performance Liquid Chromatography (Hplc), ThroughDetermining Metabolites’ Concentration In Hemolysate. Thioguanine Nucleotides (Tgn) And TheMethylated Thioinosine Derivatives Are Not Measured Directly, Rather The 6-Thioguanine (Tg) For Tgn,And 4-Amino-5-(Methylthio) Carbonyl Imidazole (Amtci) For Methylated Thioinosine Derivatives AreMeasured.There Is A Misconception Among Patients And Healthcare Providers, That Determining ThiopurineMetabolites Level Provides Assurance On Optimal Dosing Which Can Be Used To Prevent AdverseThiopurine Treatment Outcomes. Despite This Assumption, Clearly Most Of The Thiopurine AdverseEffects Are Not Directly Related To Their Metabolites As 6-Tgn Or 6-Mmp Levels. Clinical Experience HasDemonstrated That Infections Associated With Thiopurines Do Not Regularly Correlate With Leukopenia,And Elevated Transaminases Can Occur Despite Normal 6-Mmp Levels.